Fabrication and Characterization of Pluronic F68 and Phospholipon 90g Embedded Nanoformulation for Sertraline Delivery: An Optimized Factorial Design Approach and In Vivo Study - Kushwaha, Krishna; Mishra, Manoj Kumar; Srivastava, Rajat (Asian Journal of Pharmaceutical Research and Development, 2019)
Objective: The objective of present work was to utilize the potential of nanostructured lipid carriers (NLCs) form improvement in bioavailability of Sertraline as antidepressant drug formulated by emulsification- solvent evaporation technique with some modification. NLC is the blend of solid lipid, liquid lipid and surfactant for encapsulation of poor water soluble actives. Design: A full 32 factorial design was utilized to study the effect of two independent parameters namely solid lipid to liquid lipid concentration and stabilizer concentration on the entrapment efficiency of the prepared NLCs. The sertraline NLC formulation was characterized with respect to particle size, polydispersity index (PDI), zeta-potential, encapsulation efficiency and physical morphology. Result: The NLC formulation had an average diameter of 96.59 nm, PDI of 0.192, zeta-potential of -39.88 mV, and encapsulation efficiency of 97%, respectively. Conclusion: The NLC formulation for sertraline encapsulation has been successfully developed and is suitable for nose to brain delivery system due to their nano-size and sta